2018
DOI: 10.1093/jxb/ery287
|View full text |Cite
|
Sign up to set email alerts
|

Maize 16-kD γ-zein forms very unusual disulfide-bonded polymers in the endoplasmic reticulum: implications for prolamin evolution

Abstract: A prolamin paralog generated upon maize whole-genome duplication has changed its polymerization and solubility properties, allowing a new function in the assembly of maize protein bodies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 58 publications
(107 reference statements)
4
19
0
Order By: Relevance
“…For instance, maize Mucronate mutation forms a misfolded 16-kDa γ-zein that leads to irregular PB formation, but it could be rescued to restore normal PB by silencing the expression of the mutant 16-kDa γ-zein gene (34,35). Although 16-kDa γ-zein lost a large part of its N-terminal domain compared with 27-kDa γ-zein that was able to promote PB formation (36,37), a recent study showed that 16-kDa γ-zein acquired a new function in PB assembly (38). Furthermore, the 16-kDa γ-zein promoter lost all known conserved cis-elements present in other zein promoters (5) but acquired the cis-element ACGCAA, recognized by the corresponding NAC TFs, thereby restoring its endosperm-specific expression and synchronization with starch storage.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, maize Mucronate mutation forms a misfolded 16-kDa γ-zein that leads to irregular PB formation, but it could be rescued to restore normal PB by silencing the expression of the mutant 16-kDa γ-zein gene (34,35). Although 16-kDa γ-zein lost a large part of its N-terminal domain compared with 27-kDa γ-zein that was able to promote PB formation (36,37), a recent study showed that 16-kDa γ-zein acquired a new function in PB assembly (38). Furthermore, the 16-kDa γ-zein promoter lost all known conserved cis-elements present in other zein promoters (5) but acquired the cis-element ACGCAA, recognized by the corresponding NAC TFs, thereby restoring its endosperm-specific expression and synchronization with starch storage.…”
Section: Discussionmentioning
confidence: 99%
“…The increased prolamin yield in Method 2 (average 0.79 g/100 g flour) from Method 1 (0.09) indicate that teff prolamines are prone to oxidative damage and can be effectively protected by reducing agents during extraction. This protein fraction has been reported to form disulfide bonds during extraction and reducing agents effectively enhanced their extraction yield by preventing the formation of disulfide bonds [33]. Here, it can be assumed that the increase in prolamin yield is due to an increase in overall solubility and a decrease in the oxidation damage of the fraction.…”
Section: Discussionmentioning
confidence: 99%
“…Alpha and delta zeins constitute the core of the PB, whereas 27 kDa and 50 kDa gamma zeins (27γz, 50γz) form the outer PB layer, in contact with the luminal face of the ER membrane, and 16 kDa gamma zein (16γz) is at the interface between the inner core and outer PB layer [ 2 , 12 ]. 27γz, the single most abundant PB polypeptide, forms homotypic, insoluble, electron-dense PBs also when ectopically expressed in vegetative tissues [ 13 , 14 ]. Unlike α-zeins, which can be solubilized by aqueous alcohol, 27γz and 50γz are solubilized by reducing buffers; in agreement with this, progressive mutagenesis of the Cys residues involved in the interchain bonds of 27γz results in its increasing solubility and ability to traffic from the ER along the secretory pathway [ 15 ].…”
Section: Introductionmentioning
confidence: 99%